1839 Ala. Laws 67 - (:unkn) unknown (My University, 1839)
Prohibited the concealed carrying of "any species of fire arms, or any bowie knife, Arkansas tooth-pick, or any other knife of the like kind, dirk, or any other deadly weapon." Punished by fine of $50-100 and imprisonment not to exceed 3 months.
Keywords: CARRY - CONCEALED